Pengaruh Pendidikan, Kesehatan, Infrastruktur Jalan, Dan Infrastruktur Sanitasi Terhadap Ketimpangan Wilayah Di Sumatera Bagian Selatan - Naura Fahira Kesuma Putri; Dedy Yuliawan (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2026)
Regional inequality remains a regional development problem in Southern Sumatra, particularly in the provinces of Lampung, South Sumatra, and Bengkulu. Differences in the level of infrastructure development between regions lead to unequal economic development and public welfare. Education, health, road, and sanitation infrastructure are important factors influencing the level of regional inequality because they are related to public access to basic services and economic activities. This study aims to analyze the effect of education, health, road, and sanitation infrastructure development on regional inequality among the three provinces of Southern Sumatra in 2019–2023. This study uses quantitative methods with secondary data obtained from the Central Statistics Agency (BPS). Data analysis was conducted using panel data regression with the Random Effect Model (REM) approach through the RStudio application. Regional inequality was measured using the Williamson Index as an indicator of inter-regional development disparities. The results show that education infrastructure has a positive and significant effect on regional inequality. Health infrastructure has a negative and significant effect on regional inequality. Meanwhile, road and sanitation infrastructure have a negative but insignificant effect on regional inequality. These findings indicate that health infrastructure development can help reduce regional disparities, while unequal education development actually increases inequality between regions. Meanwhile, road and sanitation infrastructure development has not had a strong impact on reducing regional inequality during the study period. The study concludes that equitable infrastructure development, particularly in the education, health, road, and sanitation sectors, needs to be continuously improved to ensure more equitable development between regions and reduce regional inequality in Southern Sumatra.